Frequency And Clinical Consequences Of Hyponatremia, Hyperkalemia, And Hypocalcemia - Iqbal, Kashif; Najmuddin, Najmuddin; Abbas, Muhammad; Khalil, Ahmed Khan; Safeer, Shahid Rizwan (Journal of Neonatal Surgery, 2025)
Background: Analyzing available evidence and clinical experience shows that there are electrolyte disorders like hyponatremia, hyperkalemia, and hypocalcemia present in most hospitalized patients, and they correlate highly with the levels of morbidity and mortality associated with hospital admission. There may be a consequent series of complications related to imbalanced electrolytes, including cardiogenic, neurological, and neuromuscular complications. There are electrolyte imbalances, and once identified, they will lead to clinical incidents that worsen the patient’s overall illness or clinical condition. Therefore, electrolyte imbalances need to be corrected as soon as possible. Objectives: To ascertain the prevalence of such conditions as hyponatremia, hyperkalemia, and hypocalcemia in hospitalized patients and to analyze the neurocognitive impairments, arrhythmias, and extended length of stay, if any, that are related to these conditions. Methodology: this cross-sectional study was conducted at Department of Nephrology Prime Teaching Hospital Peshawar Pakistan from jan 2025 to june 2025. 120 hospitalized patients who underwent evaluation of their serum electrolytes were included. Monitoring of sodium, potassium, and calcium levels was performed at the time of the patient's admission. Patients' clinical outcome records were collected, including but not limited to neurological symptoms, cardiac arrhythmias, and the duration of hospital stay. Data were processed in SPSS 24.0. The significance of the results was determined based on the calculated p-value, set at 0.05 or lower, and the Chi-square test was used for statistical analysis. Results: A total of 120 hospitalized patients were assessed, with a mean age of 54.7 ± 13.2 years. The prevalence of electrolyte abnormalities was high, with hyponatremia identified in 38.3%, hyperkalemia in 25.0%, and hypocalcemia in 32.5% of cases. Hyponatremia showed a significant association with neurological manifestations such as confusion and seizures (p = 0.021). Hyperkalemia was strongly correlated with ECG changes and cardiac arrhythmias (p = 0.014). Hypocalcemia was significantly associated with muscle cramps, perioral tingling, and tetany (p = 0.030). Patients presenting with any electrolyte disturbance had a notably more extended hospital stay than those with normal electrolytes (p = 0.027), indicating a greater burden of clinical complications. Conclusion: Hyponatremia, hyperkalemia, and hypocalcemia are common electrolyte imbalances in hospitalized patients. These imbalances are intertwined with severe adverse outcomes affecting the patients' clinical conditions, reputations, hospital stays, and, in some cases, even lead to death. These electrolyte imbalances and their impacts can be efficiently managed and/or reduced through routine patient monitoring and prognostic assessment. Given that these patients are in a hospital, electrolyte monitoring should be a priority in their clinical care, particularly for those in higher-risk categories